Comparison of Goal Achievement during an Early, Intensive Nutrition Intervention Delivered to People with Upper Gastrointestinal Cancer by Telephone Compared with Mobile Application - Kate Furness; Catherine E. Huggins; Lauren Hanna; Daniel Croagh; Mitchell Sarkies; Terry P. Haines (International Journal of Telemedicine and Applications)
Objective. This study is aimed at exploring whether the mode of nutrition intervention delivery affected participant goal achievement in a three-arm randomised controlled trial of early and intensive nutrition intervention delivered to upper gastrointestinal cancer patients. Methods. Newly diagnosed upper gastrointestinal cancer patients were recruited from four tertiary hospitals in Melbourne, Australia. Participants in the intervention groups received a regular nutrition intervention for 18 weeks from an experienced dietitian via telephone or mobile application (app) using behaviour change techniques to assist in goal achievement. Univariate and multiple regression models using STATA determined goal achievement, dose, and frequency of contact between groups. A p value <0.05 was considered statistically significant. Results. The telephone group (n=38) had 1.99 times greater frequency of contact with the research dietitian (95% CI: 1.67 to 2.36, p<0.001) and 2.37 times higher frequency of goal achievement (95% CI: 1.1 to 5.11, p=0.03) compared with the mobile app group (n=36). The higher dose (RR 0.03) of intervention and more behaviour change techniques employed in the telephone group compared with the mobile app group increased participant goal achievement (95% CI: 0.01 to 0.04, p<0.001). Discussion. Telephone nutrition intervention delivery led to a higher frequency of goal achievement compared to the mobile app intervention. There was also a higher number of behaviour change techniques employed which may have facilitated the greater goal achievement. Mobile app-based delivery may have poorer acceptance in this population with high levels of withdrawal. Practice Implications. We need to ensure that specifically designed technologies for our target populations are fit for purpose, efficacious, and acceptable to both patients and healthcare providers. This trial is registered with ACTRN12617000152325.